Masculine and feminine sexuality between inactivity and effectiveness in the book “Tuhfat Al-Nuzzar” by Ibn Battuta - قدّاح رؤى (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research is based on studying Ibn Battuta’s relationship with women within the spaces of familiarity and strangeness. This relationship is considered exceptional compared to what other travelers reported about women, and the dismantling of the image of women in Ibn Battuta’s journey is achieved through our monitoring of the transformations of his male sexuality, which is based on the discourse of gender with jurisprudential reference in Arab-Islamic culture, and also through our monitoring of images of female sexuality within the two aforementioned spaces, And the conflict of sexualities in these two spaces. We presented the research with two guidance: The first is critical, presenting the differing opinions of critics about Ibn Battuta’s relationship with women, and the second is conceptual, in which we clarified the meaning of sexuality and gender discourse, the difference between them, and explained their limits and controls in Arab-Islamic culture. The research reached a number of results, including: Al-Jahiz opened the chapter on writing about sexuality in Islamic culture, and Imam Al-Ghazali’s representation of the discourse of sexuality with jurisprudential reference, and Ibn Battuta’s representation of this discourse, and the absence of effective female sexuality in the Arab space due to the dominance of this discourse, and the superiority of culture over the foreign religious factor and its formulation of its sexuality in accordance with its customs. Not with his controls.